DAMPAK MEDIASI MORAL REASONING PADA PENGARUH ORGANIZATIONAL ETHICAL CULTURE TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI - Khusnah, Hidayatul; Agustina, Heni (Universitas Nahdlatul Ulama Surabaya, 2019)
The purpose of this study is to investigate the mediating effect of moral reasoning on the influence of organizational ethical culture on the tendency of accounting fraud. This research was conducted at manufacturing companies listed in the guide book PT. SEER. The sample in this study is the financial manager or accounting manager. The number of samples in this study were 63 respondents. Total questionnaires distributed were 78 questionnaires, but as many as 65 questionnaires were returned, there were 2 questionnaires that were not filled out completely, so were excluded from testing. The hypothesis in this study was tested using Structural Equation Modeling (SEM) with an alternative method of Partial Least Square (PLS) using WarpPLS 5.0 software. The results of this study indicate that organizational ethical culture has a positive effect on moral reasoning and the tendency of accounting fraud. The next finding is moral reasoning has a positive effect on the tendency of accounting fraud.